GAS1: A New β-Glucan Immunostimulant Candidate to Increase Rainbow Trout (Oncorhynchus mykiss) Resistance to Bacterial Infections With Aeromonas salmonicida achromogenes - Cornet, Valérie; Khuyen, Trinh Dinh; Mandiki, Syaghalirwa. N. M.; Betoulle, Stéphane; Bossier, Peter; Reyes-López, Felipe E.; Tort, Lluis; Kestemont, Patrick (Frontiers in Immunology, 2021)
β-glucans are prebiotic and/or food additives used by the aquaculture industry to enhance the immune response of fish. Their efficiency may vary according to their origin and structure. In this study, the immunostimulant effects of two β-glucan types extracted from wild-type baker’s yeast (Saccharomyces cerevisiae) and its null-mutant Gas1 were investigated. Gas1 has a beta-1,3-glucanosyltransferase activity necessary for cell wall assembly. Using a positive (commercial product MacroGard®) and a negative control (a diet without glucans), we evaluated the immune responses and disease resistance of rainbow trout juveniles (mean weight ~44g) fed control, low (0.2%) and high (0.5%) doses of Macrogard®, Gas1 and Wild type-β-glucan after a short- (15 days, D15) or mid- (36 days, D36) term feeding period. We found that β-glucan supplemented diets did not affect growth performance, mortality, splenic index or leukocyte respiratory burst activity on D15 nor D36. However, each β-glucan triggered different immune effectors depending of the doses or length of exposure compared to others and/or the negative control. Indeed, high dose of MacroGard® significantly increased lysozyme activities at D15 compared to the control and other diets (p<0.05). At D36, MacroGard β-glucan enhanced the production of lymphocytes in comparison with the control diet(p<0.05). Regarding WT β-glucan, at D36, WT- β-glucan, especially the high dose, provided the highest enzymatic activities (lysozyme and ACH50) and Ig level (p<0.01). Furthermore, on D36, Gas1 also increased lysozyme activity, Ig proportion and some immune genes (mcsfra, hepcidin) compared to MacroGard® (p<0.05). Besides, both doses of Gas1-β-glucans increased the resistance of juveniles to bacterial infection highlighted by a higher survival rate at 14 days post-challenge compared to the control and other types and doses of β-glucans (p<0.05). In conclusion, our results suggest that Gas1-β-glucan could represent a promising immunostimulant that would help to prevent diseases in aquaculture even more efficiently than other β-glucans already in use. Mode of action and particular efficiency of this new Gas1 mutant are debated.